PELUANG URBAN FARMING UNTUK MENINGKATKAN KETAHANAN PANGAN WILAYAH RENTAN BANJIR DI KELURAHAN BANDENGAN KOTA PEKALONGAN - Ari Handriatni; Sajuri Sajuri (LPPM Universitas Pekalongan, 2021)
Bandengan village is one of the northern coastal areas of Pekalongan which has been affected by tidal flooding until now. The tidal flood conditions forced people whose livelihoods were from agriculture to change into casual laborers, traders and so on. There is a need for technological breakthroughs in carrying out agricultural activities that are minimal and unsupportive. The modern term that is currently used to cover several cultivation methods in urban areas is Urban Farming. Urban Farming is a form of urban farming growing food in urban areas on land, usually in backyards or on vacant lots, but sometimes neglected spaces such as road medians, which are not usually dedicated to producing food. Extension activities and mentoring by competent agriculture can be able to change conditions that are less favorable for agricultural cultivation until the community is ready in terms of theory and practice. This service is in the context of the 40th anniversary of Pekalongan University in the context of forming the target village. The methods used in this service are lectures, active participation or discussion and mentoring. The outreach activities in the form of lectures and discussions were attended by the youth of the Bandengan village. An overview of Urban Farming is presented using a projector. The explanation of the Urban Farming concept offered is in accordance with the Bandengan area (verticulture, hydroponics, aquaponics and polybags) and what has been done by Bandengan residents, namely hydroponics and polybags. The implementation of this counseling has an impact on the community's enthusiasm to carry out agricultural activities even though their agricultural land has been submerged by tidal water. Urban farming explains how cultivation on land is limited and affected by tidal flooding but can still produce vegetable and fruit crops that can increase the income of the people of Bandengan village.Keywords : Agriculture, Bandengan, Flood Rob, Urban Farming